1998
DOI: 10.1093/jac/42.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a novel, inhibitor-potentiated disc-diffusion test with other methods for the detection of extended-spectrum beta-lactamases in Escherichia coli and Klebsiella pneumoniae

Abstract: A novel, inhibitor-potentiated disc-diffusion test for detecting extended-spectrum beta-lactamases (ESBLs) in bacteria was evaluated. This test uses the principle of augmentation (by > or = 10 mm) of inhibition zones produced by ceftazidime, cefotaxime, ceftriaxone or aztreonam discs on Mueller-Hinton agar supplemented with clavulanate (4 mg/L). The test was initially compared with the double-disc synergy test, Kirby-Bauer disc-diffusion test and Etest ESBL screen with a panel of 45 reference strains with know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 15 publications
2
38
0
1
Order By: Relevance
“…In a review of studies which have evaluated collections of ESBL-producing organisms using standard CLSI disk diffusion or MIC breakpoints, 13 to 49% of isolates were cefotaxime susceptible, 36 to 79% ceftriaxone susceptible, 11 to 52% ceftazidime susceptible, and 10 to 67% aztreonam susceptible. Approximately 40% tested susceptible to at least one oxyimino ␤-lactam and 20% to all oxyimino ␤-lactams (91,94,165,179,289,393,409). The reasons for this apparent susceptibility to some cephalosporins is the result of various degrees of hydrolysis of cephalosporins by different ␤-lactamases and enhanced penetration through the bacterial outer membrane of some cephalosporins compared to others.…”
Section: Need For Clinical Microbiology Laboratories To Detect Esbl Pmentioning
confidence: 99%
“…In a review of studies which have evaluated collections of ESBL-producing organisms using standard CLSI disk diffusion or MIC breakpoints, 13 to 49% of isolates were cefotaxime susceptible, 36 to 79% ceftriaxone susceptible, 11 to 52% ceftazidime susceptible, and 10 to 67% aztreonam susceptible. Approximately 40% tested susceptible to at least one oxyimino ␤-lactam and 20% to all oxyimino ␤-lactams (91,94,165,179,289,393,409). The reasons for this apparent susceptibility to some cephalosporins is the result of various degrees of hydrolysis of cephalosporins by different ␤-lactamases and enhanced penetration through the bacterial outer membrane of some cephalosporins compared to others.…”
Section: Need For Clinical Microbiology Laboratories To Detect Esbl Pmentioning
confidence: 99%
“…The antibacterial activities of C. edulis extract were determined using the antibiotic disc diffusion assay ("Kirby-Bauer" assay) [10]. Briefly, bacterial strains (E. coli, B. diminuta, B. magaterium and M. luteus) were grown at 37°C in Luria-Bertani broth and their optical density adjusted to 1.0 at 595 nm.…”
Section: Antibacterial Testmentioning
confidence: 99%
“…The crude metanolic extract of C. edulis were tested against bacteria and yeast using the disc diffusion assay [10]. The results revealed that C. edulis extract inhibited growth of B. diminuta, M. luteus and B. magaterium.…”
Section: Edulis Extracts Exhibited Antibacterial But No Antifungalmentioning
confidence: 99%
“…Unfortunately, many Enterobacteriaceae producing these new ␤-lactamases do not show frank resistance in routine susceptibility tests with certain ␤-lactam antibiotics despite clinical evidence that the drugs do not provide effective therapy (8,10,21,29,44). Thus, it has become imperative to design tests that will help microbiologists identify which ␤-lactamase(s) may be present in a clinical isolate of Enterobacteriaceae (8,11,12,17,20,25,33,34,(38)(39)(40).A series of studies have been performed to determine whether or not results of microdilution panels with or without ␤-lactamase inhibitors could be used to determine the presence of certain ␤-lactamases among species within the family Enterobacteriaceae (13,25,41). Results have shown that a broad variety of ␤-lactam drugs would be required for a ␤-lactamase identification panel and that accurate identification would require complex logic pathways involving multiple drugs.…”
mentioning
confidence: 99%
“…Unfortunately, many Enterobacteriaceae producing these new ␤-lactamases do not show frank resistance in routine susceptibility tests with certain ␤-lactam antibiotics despite clinical evidence that the drugs do not provide effective therapy (8,10,21,29,44). Thus, it has become imperative to design tests that will help microbiologists identify which ␤-lactamase(s) may be present in a clinical isolate of Enterobacteriaceae (8,11,12,17,20,25,33,34,(38)(39)(40).…”
mentioning
confidence: 99%